Magnitude de pronação do pé afeta movimento pélvico na fase de resposta à carga da marcha - Joana Ferreira Hornestam (2015)
Increased foot pronation during walking has been associated with low back pain. This association may be mediated by the impact of increased pronation on pelvic motion. This study investigated the effects of increased bilateral foot pronation on the pelvic kinematic during walking. Kinematic variables of pelvis and foot of 20 participants were collected while they walked on a treadmill in a fast walking speed (5km/h), wearing flat and medially inclined insoles inserted in walking shoes. Pelvic movement in the frontal and transverse planes was analyzed during loading response phase of gait and foot eversion-inversion during stance phase in order to verify the effectiveness of medially inclined insoles in inducing increased pronation and to make it possible to identify and exclude excessive pronators and verify. Medially inclined insoles were effective in inducing increased foot pronation throughout stance phase. Increased pronation altered pelvic motion. In the frontal plane, pelvic mean position was more inclined to the contralateral side and the amplitude of movement reduced when increased pronation was induced, in comparison to the control condition. In the transverse plane, pelvic mean position was less rotated toward the contralateral leg in increased pronation condition, in comparison to the control condition, and the amplitude of movement was not statistically different between conditions. Bilateral increased pronation affects pelvic kinematic during walking and can be potentially related to the development of low back pain as it may increase stresses to spinal and sacroiliac joints.